Digital Audio and Podcasting. Some Educational Applications - Aranzubia Cob, Asier; Gallego Pérez, Juan Ignacio (Estudios sobre el Mensaje Periodístico, 2013)
This paper analyzes the evolution of the production and distribution of digital audio carried out by the university community members. We start from the general framework of the audio content diffusion in university environment. Then, the text approaches to different innovative education experiences through this media. Finally, it focuses on the case study of the Film Studies subject that uses digital audio as a mediation tool in the Universidad Carlos III de Madrid.
Keywords: podcasting; digital audio; Film Studies; EEES; innovation